Growth Inhibition and Apoptosis with H31 Metabolites from Marine Bacillus SW31 in Head and Neck Cancer Cells - Lim, Young Chang; Cho, K. Woong; Kwon, Hak Cheol; Kang, Sung Un; Pyun, Jung Hee; Lee, Mi Hye; Hwang, Hye Sook; Kim, Jang Hee; Lee, Ha Neul; Choi, Eun Chang; Kim, Chul-Ho (KOREAN SOC OTORHINOLARYNGOL, 2010)
Objectives. To determine whether a novel marine micro-organism with anticancer properties, H31, the metabolic product of Bacillus SW31, has anti-tumor effects on head and neck cancer, and potential for apoptotic-enhancing anti-cancer treatment of affected patients. Methods. The cell viability and apoptosis assays were performed. Changes in the signal pathway related to apoptosis were investigated. Then, the therapeutic effects of H31 were explored in mouse xenograft model and drug toxicity of H31. was examined in zebrafish model. Results. We identified the anticancer activity of H31, a novel metabolic product of Bacillus SW31. Bacillus SW31, a new marine micro-organism, has 70% homology with Bacillus firms and contains potent cytotoxic bioactivity in head and neck cancer cells using MU assay. Combined with c-JUN, p53, cytochrome C, and caspase-3, H31 induced apoptosis of KB cells, a head and neck cancer cell line. In a separate in vivo model, tumor growth in C3H/HeJ syngeneic mice was suppressed by H31. In addition, in a zebrafish model used for toxicity testing, a considerable dose of H31 did not result in embryo or neurotoxicity. Conclusion. Growth inhibition and apoptosis were achieved both in vitro and in vivo in head and neck cancer cells after exposure to H31, a metabolite from the marine Bacillus species, without any significant toxicity effects even at considerable H31 dose concentrations.